Photo‐responsive block copolymer containing azobenzene group: Synthesis by reversible addition‐fragmentation chain transfer polymerization and characterization. Issue 33 (29th April 2019) - Yang, Runmiao; Liu, Yuhai; Chen, Jianxiang; Zhu, Wen; Dong, Guanxiu
ABSTRACT: The design and synthesis of a new azobenzene‐based methacrylate monomer (Azo‐IEM) was demonstrated, and its polymerization behavior during reversible addition‐fragmentation chain transfer (RAFT) polymerization was investigated. Well‐defined homopolymer and amphiphilic block copolymer containing Azo‐IEM monomeric units were successfully prepared as evidenced by NMR and GPC analysis. Moreover, the photo‐triggered reversible isomerization of polymer products in selected solvents was investigated. Finally, TEM analysis showed that there were significant differences in the nanoparticle morphologies when the block copolymer samples were irradiated with different wavelengths of light (i.e., UV and visible). The size and shapes of the p(HEMA‐ b ‐Azo‐IEM) polymer capable of transitions upon changes in Vis/UV light exposure which prepared from MeOH/CHCl3 mixture solvent. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47870. Abstract : The size and shapes of the p(HEMA‐ b ‐Azo‐IEM) polymer capable of transitions upon changes in Vis/UV light exposure which prepared from MeOH/CHCl3 mixture solvent.